The Concept of Learning Maharah Istima according to Ali Ahmad Madkur - Muhammad Iqbal Trenggono; R. Umi Baroroh; ABD. Rauf Tan Sri Hassan (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2023)
This study aimed to explore more deeply the concept of learning maharah istima Ali Ahmad Madkur. The research is qualitative descriptive research, using qualitative analysis strategy techniques and library research methods. The results showed the concept of learning maharah istima presented by Ali Ahmad Madkur, starting from the essence of maharah istima, the general purpose of learning istima, the objectives and skills of maharah istima at the beginner level, the division of istima, the learning program of istima, and strategies and stages that must be done in maharah istima. The success of Arabic language learning in maharah istima can be achieved when the learning contains meta-cognitive, social-affective, and psychomotor elements. Ali Ahmad Madkur's concept includes meta-cognitive and psychomotor aspects. However, seeing that the affective aspect is not found in Ali Ahmad Madkur's concept, the affective aspect is very important to complement Ali Ahmad Madkur's concept because the affective aspect is very influential on the emotional relationship between teachers and students.